The International treaty on plant genetic resources for food and agriculture: A primer for the future of CGIAR: prepared to assist the Future Harvest Centres in understanding and preparing for implementation of the Treaty - Fowler, Cary; Moore, G.; Hawtin, Geoffrey C.; CGIAR Systemwide Genetic Resources Programme; International Plant Genetic Resources Institute (2003)
The Treaty establishes a Multilateral System for access and benefit-sharing. This system applies to 35 crops (and crop complexes) and a number of forages. Facilitated access will be granted to materials within that Multilateral System. Conditions of access, including benefitsharing requirements, will be contained in a yet-to-be-finalized Material Transfer Agreement, consistent with provisions provided in the Treaty. Article 15 of the Treaty specifically addresses the collections held by the Future Harvest Centres supported by the CGIAR, and those held by other international institutions. It reconfirms their status as materials held 'in trust' and specifies how access to and benefit-sharing associated with these materials will be handled in the future under the Treaty. Centres are invited to conclude agreements with the Governing Body of the Treaty in order to bring the collections formally under the auspices of the Treaty. This guide, prepared primarily as a reference document for the CGIAR, examines the text of the Treaty in detail. It focuses on how the Multilateral System will operate, and on the obligations Centres would assume under the Treaty. It identifies areas of ambiguity, as well as issues that remain to be resolved by the Treaty's Governing Body. A timetable is also provided, which summarizes the deliberations and actions that would need to take place to meet the requests of FAO and to formalize Centres' association with the Treaty.